A guide to hands-on MEMS design and prototyping - Kubby, Joel A. (Cambridge University Press, 2011)
"Whether you are a student taking an introductory MEMS course or a practising engineer who needs to get up to speed quickly on MEMS design, this practical guide provides the hands-on experience needed to design, fabricate and test MEMS devices. You will learn how to use foundry multi-project fabrication processes for low-cost MEMS projects, as well as computer-aided design tools (layout, modeling) that can be used for the design of MEMS devices. Numerous design examples are described and analysed, from fields including micro-mechanics, electrostatics, optical MEMS, thermal MEMS and fluidic MEMS. There's also a final chapter on packaging and testing MEMS devices, as well and exercises and design challenges at the end of every chapter. Additional resources are provided online, including solutions to the design challenge problems and a selection of case studies of MEMS devices"-- Provided by publisher.
Keywords: Microelectromechanical systems.; elektronické knihy; electronic books